The first complete mitochondrial genome of Eucommia ulmoides: a multi-chromosomal architecture and controversial phylogenetic relationship in asterids - Meng Li; Weijie Zhao; Jing Qiu; Changwei Bi (BMC Plant Biology)
Abstract Background Eucommia ulmoides (E. ulmoides) is the sole representative of the Eucommiaceae family, exhibiting abundant medical application as traditional Chinese medicine and high commercial application as a hardy rubber tree. Although some high-quality nuclear genomes and plastid genomes (plastome) have been reported, a comprehensive analysis of its complete mitochondrial genome (mitogenome) remains lacking. Results In this study, we successfully assembled the first complete mitogenome of E. ulmoides based on PacBio HiFi sequencing data. The architecture of E. ulmoides mitogenome exhibited two circular chromosomes (MC1 and MC2) with a combined length of 541.7 kb. A total of 61 genes were annotated in the E. ulmoides mitogenome, including 38 unique protein-coding genes (PCGs), 21 tRNA genes, and 2 rRNA genes. We found that the dispersed repetitive sequences comprised 21.67% of the mitogenome with the largest repeat spanning > 16 kb. The collinearity of E. ulmoides mitogenome with other species was relatively low with the longest homologous sequence being only 5,960 bp. The phylogenetic trees constructed based on mitogenomes and plastomes, respectively, consistently confirmed that E. ulmoides belongs to the basal lamiid clade, which is congruent with the APG IV classification system. The PCG composition of mitogenomes across four major lineages of land plants (liverworts, ferns, gymnosperms, and angiosperms) demonstrated the convergent reduction in mitogenomic evolution. Conclusions We reported the latest mitogenome of E. ulmoides with a two-circular chromosomal architecture obtained through PacBio HiFi reads, which was the first mitogenome in the genus Eucommia and the order Garryales to be described in detail. The mitogenome of E. ulmoides provided a solid foundation for comprehending the evolutionary trajectories and elucidating the underlying causes of cytonuclear discordance in E. ulmoides.